Great Bricett Manor and Priory. Lords, Saints and Canons in a Suffolk Landscape - Christie, Neil (Medieval Settlement Research, 2023)
A number of years in the making, this well-researched volume was prompted by the owners of Great Bricett Hall (who formerly held the title of Lord of the Manor, purchased by auction in 1996, but transferred in perpetuity to Great Bricett Parochial Church Council in 2017). The first lords, detailed in Chapter 3, were Norman knights: Ranulf Peverel was a high-ranking tenant-in-chief for William the Conqueror for lands between Norfolk, Suffolk, Essex and Oxfordshire – sizeable holdings, though Ranulf is only ranked as a ‘Class C’ magnate by modern scholars (p.13); at the time of the Domesday Book in 1086 one Ralph fitz Brien appears as Ranulf’s tenant, holding the manor at Bricett, displacing a Saxon lord, Leoftsan. Ralph and his wife, at the encouragement of the bishop of Norwich and others, established a nearby priory of Augustinian Canons between 1114–19 (figs. 6.9 and 6.10 illustrate the priory’s foundation charter and a seal of c. 1190). In a charter of 1152–54 the market at Great Bricett was granted by King Stephen to the priory (pp.73–4; charter illustrated as fig. 6.11).